Land Dynamics And Issues Of Social Inclusion: Rethinking Sustainable Metropolitanization Of Greater Lomé Beyond Institutional Constraints - Koudjo, AIDAM (Journal of Ecohumanism, 2025)
Greater Lomé is experiencing rapid population growth and significant urban expansion. Covering an area of 425.6 km², it has a density of only 71 inhabitants per hectare, posing substantial institutional challenges to sustainable metropolitan development. This study examines how land transformations can reimagine social inclusion beyond institutional barriers. By combining diachronic spatial analysis with field surveys of 290 households and 50 key stakeholders, we identified a socio-spatial divide characterized by high informality and inadequate infrastructure: access to potable water declines from 85% in the city center to just 30% in vulnerable neighborhoods. Although the real estate market is predominantly cash-driven (65% of transactions) and facilitates property acquisition in the outskirts (with 75% of peri-urban households owning property), this process often operates outside legal norms. This is attributed to the lengthy and costly registration procedures, ranging from 500,000 to 800,000 FCFA, which perpetuate informality in the land sector. Ultimately, the metropolis is fragmented, necessitating the urgent establishment of a hybrid governance model to operationalize new institutions and ensure coordinated planning, integrating informality as a mechanism for land security towards a more inclusive city.